Diskursus Penundukan Prajurit TNI pada Peradilan Umum - Tiarsen Buaton; Prastopo Prastopo; Agustinus Purnomo Hadi; Ateng Karsoma; Mulyono Mulyono; M. Ali Ridho (Penerbit Goodwood, 2024)
Purpose: Pros and cons about the position and jurisdiction of military courts still often occur in legal discourse in Indonesia. On the one hand, there are groups that state that military courts are only authorized to try military crimes and are not authorized to try general crimes committed by TNI soldiers, but other groups state that military courts still have the authority to try both general and military crimes. This article will capture the discourse that has existed so far. This article will also explain about the Position and Jurisdiction of Military Courts in Indonesia after being under the authority of the Supreme Court and the impact of the submission of TNI soldiers to the General Court on military principles. Method: The method used is an in-depth interview with a number of sources, especially to see the opinions that develop if TNI soldiers are tried in the general court. Result: The conclusion of this article is that psychologically and culturally, TNI soldiers are not appropriate to be tried in general courts. Thus the issue of submission of TNI soldiers to the general court is not only juridical but also psychological and cultural. In addition, if TNI soldiers are subject to the general court, this will result in the destruction of the joints or principles of the military which are the backbone of law enforcement and discipline of Soldiers.